2014
DOI: 10.1155/2014/679678
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on Dynamic Crushing Behavior of Auxetic Honeycombs with Various Cell-Wall Angles

Abstract: Auxetic honeycombs have proven to be an attractive advantage in actual engineering applications owing to their unique mechanical characteristic and better energy absorption ability. The in-plane dynamic crushing behaviors of the honeycombs with various cellwall angles are studied by means of explicit dynamic finite element simulation. The influences of the cell-wall angle, the impact velocity, and the edge thickness on the macro/microdeformation behaviors, the plateau stresses, and the specific energy absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 34 publications
4
44
0
Order By: Relevance
“…As mentioned in section ''Most appropriate strain,'' all s-e curves have four different phases: linear elastic phase, yield phase, flat plateau stress phase, and densification phase, which are similar to the curve patterns of other 2D honeycombs, [28][29][30][31][32][33][34][35][36][37][38][39][40][41] even though the s-e curves have different characteristics at different crushing velocities. Mean quasi-static and dynamic plateau stresses are discussed in detail in section ''Mean plateau stress.''…”
Section: Reliability Of Fe Modelmentioning
confidence: 64%
See 1 more Smart Citation
“…As mentioned in section ''Most appropriate strain,'' all s-e curves have four different phases: linear elastic phase, yield phase, flat plateau stress phase, and densification phase, which are similar to the curve patterns of other 2D honeycombs, [28][29][30][31][32][33][34][35][36][37][38][39][40][41] even though the s-e curves have different characteristics at different crushing velocities. Mean quasi-static and dynamic plateau stresses are discussed in detail in section ''Mean plateau stress.''…”
Section: Reliability Of Fe Modelmentioning
confidence: 64%
“…Owing to the advantages of FE simulations over experiments, the FE numerical method has been solely and widely used in the investigations of 2D honeycombs. [28][29][30][31][32][33][34][35][36][37][38][39][40][41] The existing investigations have shown that the configuration parameters and crushing velocity affect the dynamic behaviors of 2D honeycombs. The typical configuration of the MRACHs (with 9 3 9 cells in directions x 1 and x 2 ) is shown in Figure 1 In this article, the in-plane (direction x 2 or x 1 in Figure 1) crashworthiness of MRACHs is investigated numerically using the explicit FE analysis software, ANSYS/LS-DYNA, at the crushing velocities 1-250 m/s.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of cell-wall alignment on the dynamic responses of a re-entrant honeycomb structure was studied by Zhang et al, [ 23 ]. It was recognized that increasing the impact speed, cell angle and relative density leads to increasing the crashworthiness capability of the auxetic structure.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of cellular geometries, that give auxetic behaviour, are double arrow-head [33], re-entrant [34], chiral [35], and rotating rigid units [36]. They are used to produce foams or auxetic cellular metals, for a wide range of applications, such as aerospace, biomedical and military engineering [37].…”
Section: Introductionmentioning
confidence: 99%